Pengaruh Kompensasi Dan Kepemimpinan Terhadap Kinerja Karyawan - Monica Evriliani; Ahmad Gunawan (Jurnal Ekonomi dan Bisnis Digital, 2023)
The increase in insurance throughout 2022-2023 has been a remarkable achievement. This result states that people are increasingly realizing the importance of life insurance as a form of future financial planning. Every company has a goal to succeed, one way for a company to survive is to improve its performance, especially in the field of HR (human resources). Employee performance is influenced by several factors such as compensation and leadership. The purpose of this study is to examine the effect of compensation and leadership on employee performance. The method used is comparative causality, which is to investigate possible causal relationships based on observations of existing effects and using certain data to find facts that have the potential to cause causation. Based on the research results, compensation has a positive influence on employee performance at PT AJS Bumiputera Syariah Yogyakarta, leadership has a positive influence on employee performance at PT AJS Bumiputera Syariah Yogyakarta, compensation and leadership have a positive influence on employee performance